Let $f: R -\{3\} \rightarrow R -\{1\}$ be defined by $f(x)=\frac{x-2}{x-3} .$ Let $g: R \rightarrow R$ be given as $g ( x )=2 x -3$. Then, the sum of all the values of $x$ for which $f^{-1}( x )+ g ^{-1}( x )=\frac{13}{2}$ is equal to ...... .

  • [JEE MAIN 2021]
  • A

    $7$

  • B

    $2$

  • C

    $5$

  • D

    $3$

Similar Questions

Which of the following functions is inverse of itself

The inverse of the function $\frac{{{{10}^x} - {{10}^{ - x}}}}{{{{10}^x} + {{10}^{ - x}}}}$ is

It is easy to see that $f$ is one-one and onto, so that $f$ is invertible with the inverse $f^{-1}$ of $f$ given by $f^{-1}=\{(1,2),(2,1),(3,1)\}=f$

If $f: R \rightarrow R$ be given by $f(x)=\left(3-x^{3}\right)^{\frac{1}{3}},$ then $fof(x)$ is ..........

Let f : $R \to R$ be defined by $f\left( x \right) = \ln \left( {x + \sqrt {{x^2} + 1} } \right)$ , then number of solutions of $\left| {{f^{ - 1}}\left( x \right)} \right| = {e^{ - \left| x \right|}}$ is